Different influences on lexical priming for integrative, thematic, and taxonomic relations - Jones, Lara L.; Golonka, Sabrina (Frontiers in Human Neuroscience, 2012)
Word pairs may be integrative (i.e., combination of two concepts into one meaningful entity; e.g., fruit - cake), thematically related (i.e., connected in time and place; e.g., party - cake), and/or taxonomically related (i.e., shared features and category co-members; e.g., muffin - cake). Using participant ratings and computational measures, we demonstrated distinct patterns across measures of similarity and co-occurrence, and familiarity for each relational construct in two different item sets. Overall, target RTs and priming magnitudes were consistent across the SOAs for both item sets. However, results of a standard lexical decision task with various delays between prime and target presentation further demonstrated distinct patterns among these three relations on some of the underlying measures influencing target word recognition (LSA, Google, and BEAGLE). These distinct patterns suggest different mechanisms of lexical priming and further demonstrate that integrative relations are distinct from thematic and taxonomic relations.